Laparoscopic management of endometrial stromal sarcoma in young: a case report - Puntambekar, Shailesh; Shankar, Shetty Theertha; Goel, Arjun; Panchal, Shakti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Endometrial stromal sarcoma (ESS) is a case malignancy and accounts for 0.2% of all uterine malignancies and 10% of all uterine sarcomas. In the present case, an unmarried 27-year-old woman presented with complaints of on and off episodes of pain in the lower abdomen. On examination, a diffuse oval mass was felt occupying the hypogastrium, iliac and lumbar regions and extending up to the umbilicus. CT scan impression was given as? Complex retroperitoneal mass? solid cystic ovarian mass with grade I right hydro nephrosis. On laparoscopy, a huge mass measuring approximately 10×10 cm was noted arising from the uterus. Laparoscopic myomectomy was done and the specimen was retrieved in a bag and the tissue was sent for histopathological examination. The postoperative clinical course was uneventful. The patient was advised to undergo oocyte cryopreservation following which she was advised hysterectomy with bilateral salphingo-oophorectomy. Pelvic radiation was advised thereafter. ESS is a rare malignant tumor, which on histopathological examination reveals sheets of cells and endometrial stromal cell differentiation. Hysterectomy with bilateral salpingo-oophorectomy is optimum initial therapy. Radiotherapy is chosen when the tumour is inadequately excised or the pelvic disease is locally recurrent. Low grade ESS is a rare form of uterine sarcoma usually seen between 40-60 years of age with limited available data regarding the clinical course and management. Early diagnosis and management is associated with a favourable prognosis and outcome.